1995
DOI: 10.1111/j.1365-2486.1995.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of elevated CO2 on community structure, biomass and carbon balance of mediterranean old‐fleld microcosms

Abstract: We studied the effects of a doubling of atmospheric CO2 concentration on intact monoliths of Mediterranean grassland in growth chambers where climatic field conditions were simulated. During the six month growing season, changes in community structure were monitored by quantifying species richness and cover. The CO2 exchange of microcosms was measured continuously and the resulting quantity and quality of biomass were evaluated. Species richness and cover did not respond to elevated CO2. After one month of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
(22 reference statements)
5
40
1
Order By: Relevance
“…Most studies with undisturbed natural grassland communities under elevated CO 2 have yielded only marginally and frequently not signi®cant increases in community-level biomass (Owensby et al 1993;Navas et al 1995;Wolfenden and Diggle 1995). We observed a small increase (+6%) in aboveground community biomass in the ®rst, and a much larger increase (+26% ) in the second year of our experiment.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Most studies with undisturbed natural grassland communities under elevated CO 2 have yielded only marginally and frequently not signi®cant increases in community-level biomass (Owensby et al 1993;Navas et al 1995;Wolfenden and Diggle 1995). We observed a small increase (+6%) in aboveground community biomass in the ®rst, and a much larger increase (+26% ) in the second year of our experiment.…”
Section: Discussioncontrasting
confidence: 47%
“…Leadley and StoÈ cklin (1996), however, observed signi®cant genetic variation in CO 2 response within this species, including positive-and negative-responding genotypes. In a study by Navas et al (1995) with monoliths from dry Mediterranean grasslands, growth of B. erectus was stimulated under elevated CO 2 . Also during the third year of exposure to elevated CO 2 at the site of origin of our monoliths, a moderately positive e ect of CO 2 enrichment became apparent in this species, exclusively due to enhanced tillering (Leadley et al unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all these experiments were carried out under fertile, horticultural or agronomic conditions not representative for natural plant communities where other nutrients such as P may limit legume growth. In contrast Navas et al (1995) working with unfertilized intact mediterranean grassland sods found no CO 2 response of legumes.…”
Section: Introductionmentioning
confidence: 86%
“…The data we present here add to a growing body of literature that suggest that, when whole communities are examined, rather than individual plants growing in pots in ideal conditions. increases in below-ground production are more likely than effects above ground (Arnone & Korner, 1995, Dhillioii & Roy, 1996Drake et al, 1996), This pattern is not universal-Studies in which no or little response to CO,^ are reported (Navas et al, 1995) are perhaps less often published than those which give clear-cut results, as can be seen by studying the report of a GCTE meeting by Canadell et al (1996), It is difficult to generalize from these results, but when taken with the meta-analysis by Rogers et al (1996) that demonstrates a w^idely-observed tendency for root grow^th to be stimulated under elevated CO^, it seems likely that root bionnass will accumulate in many ecosystems. Even so.…”
Section: Respirationmentioning
confidence: 99%